1993
DOI: 10.1007/bf01923958
|View full text |Cite
|
Sign up to set email alerts
|

Queen success is correlated with worker-brood genetic relatedness in a primitively eusocial wasp (Ropalidia marginata)

Abstract: Abstract. Ropalidia marginata is a primitively eusocial polistine wasp in which, although there is only one queen at any given time, frequent queen replacements lead to a system of serial polygyny. One of the most striking features of this system is the enormous variation in the success of different queens. Measuring queen success as queen tenure, total number of offspring produced, number of offspring produced per day of tenure, and proportion of eggs laid that develop into adults, we show here that each meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Moreover, overall group productivity was positively associated with r, as predicted by tug-of-war models. This association, which has previously been reported in some other social insects 20 , is expected from the lower investments in reproductive competition in groups where individuals are more related because of kin benefits. Finally, we also found that the tendency of females to join another female was significantly influenced by their relatedness: in the high-relatedness treatment, where females could readily associate with related individuals, the bees founded 33 multi-female and 30 single-female nests, versus 5 multifemale and 52 single-female nests in the low-relatedness treatment (two-sided Fisher's exact test, P , 0.0001).…”
supporting
confidence: 78%
“…Moreover, overall group productivity was positively associated with r, as predicted by tug-of-war models. This association, which has previously been reported in some other social insects 20 , is expected from the lower investments in reproductive competition in groups where individuals are more related because of kin benefits. Finally, we also found that the tendency of females to join another female was significantly influenced by their relatedness: in the high-relatedness treatment, where females could readily associate with related individuals, the bees founded 33 multi-female and 30 single-female nests, versus 5 multifemale and 52 single-female nests in the low-relatedness treatment (two-sided Fisher's exact test, P , 0.0001).…”
supporting
confidence: 78%
“…Our results contrast with findings from other social insects, which show variable queen turnover rates. The serial polygynous wasp, Ropalidia marginata , showed frequent queen replacements, up to 10, throughout the year without a clear relation with the colony cycle (Gadagkar et al, 1993). Among Polistes wasps, dominance behavior is commonplace, where a single queen dominates the reproduction of the colony.…”
Section: Discussionmentioning
confidence: 99%
“…This indirect communication in a self-organizing emergent system, where its individual parts communicate with one another by modifying their local environment, is called stigmergy (Abraham, Grosan & Ramos, 2006;Grassé, 1959). The most familiar examples of stigmergy, in natural systems, are observed in ants, bees, wasps, fish school, bird flocks, animal herds, and so on (Brothers, 1999;Gadagkar, 1993). It is this coordination mechanism used by these insects and other social animals that has inspired researchers to develop plenty of metaheuristic computing algorithms.…”
Section: Introductionmentioning
confidence: 99%